Effect of chia mucilage addition on oxidation and release kinetics of lemon essential oil microencapsulated using mesquite gum – Chia mucilage mixtures. (February 2019) - Cortés-Camargo, Stefani; Acuña-Avila, Pedro Estanislao; Rodríguez-Huezo, María Eva; Román-Guerrero, Angélica; Varela-Guerrero, Victor; Pérez-Alonso, César
Abstract: Lemon essential oil (LEO) emulsions were prepared using mesquite gum (MG) - chia mucilage (CM) mixtures (90-10 and 80-20 MG-CM weight ratios) and MG as control sample, LEO emulsions were thenspray dried for obtaining the respective microcapsules.LEO emulsions were analyzed by mean droplet size and apparent viscosity, while microcapsules were characterized through mean particle size, morphology, volatile oil retention (≤51.5%), encapsulation efficiency (≥96.9%), as well asoxidation and release kinetics of LEO. TheLEO oxidation kinetics showed that 90–10 and 80–20MG-CM microcapsules displayed maximum peroxide values of 91.6 and 90.5 meq hydroperoxides kg −1 of oil, respectively, without significant differences between them ( p  > .05).MG-CM microcapsules provided better protection to LEO against oxidation than those formed with MG; where the oxidation kinetics were well adjusted to zero-order (r 2  ≥ 0.94).The LEO release kinetics from microcapsules were carried out at differentpH (2.5 and 6.5) and temperature (37 °C and 65 °C) and four mathematical models (zero-order, first-order, Higuchi and Peppas) were used to evaluate the experimental data; the release kinetics indicated that the 80-20 MG-CM microcapsules had a longer delay in LEO release rate, followed by 90-10 MG-CM and MG microcapsules, hence, CM addition in MG-CM microcapsules contributed to delay the LEO release rate. This work clearly demonstrates that use of a relatively small amount of CM mixed with MGimproves oxidative stability and delays the release rate of encapsulated LEO regarding MG microcapsules, therefore, MG-CM mixtures are interesting additives systems suitable for being applied in food industry. Graphical abstract: Unlabelled Image Highlights: Mesquite gum (MG) - Chia mucilage (CM) mixtures were used to encapsulate lemon oil. MG-CM emulsions had larger droplet size and higher viscosity than MG emulsions. MG-CM microcapsules had better oil oxidative stability at 35 °C than MG microcapsules. MG-CM microcapsules had slower oil release rates than MG microcapsules. MG-CM microcapsules had better functional characteristics than MG microcapsules.